Achieving the same educational opportunities for all: overcoming hoax interpretations of the PISA results - Carme Garcia Yeste; Teresa Morlà-Folch; Garazi Lopez de Aguileta; Laura Natividad Sancho; Ane Lopez de Aguileta; Ariadna Munté-Pascual (International Journal of Adolescence and Youth)
Despite discourses in the media and by some ‘experts’ that claim that students’ socioeconomic and migration status determine academic achievement, research has already shown that these are only correlations and that what determines academic achievement are the actions implemented in a school. Research has provided evidence of Successful Educational Actions (SEA) that have achieved excellent results among all students in very diverse contexts. This study delves into the absenteeism and academic performance of a primary and secondary school located in a marginalized neighbourhood in Spain that has been implementing SEA. Researchers have gathered data on the results of basic competencies in sixth grade in primary education and the evolution of absenteeism between the 2021–2022 and 2022–2023 school years. Results show that a school with a majority of students with a disadvantaged socio-economic profile improves its results by applying SEA and demonstrating how to overcome school failure.